Effects of EduCube Inquiry-Based Learning on Elementary Students' Cube Spatial Visualization, Learning Interest, and Mathematics Achievement: A Quasi-Experimental Study - Dwi Cahyanti Alfiah; Achmad Buchori; Lina Putriyanti (Jurnal Pendidikan Terapan, 2026)
Spatial visualization is fundamental for elementary geometry learning, yet many students struggle to interpret three-dimensional cube structures because instruction remains dominated by teacher-centered approaches and two-dimensional representations. Although inquiry-based learning, concrete manipulatives, and spatial reasoning have shown educational outcomes, limited empirical evidence has examined their integration while simultaneously investigating students' spatial visualization, learning interest, and mathematics achievement. Accordingly, this study investigated the effects of inquiry-based learning assisted by colorful cube manipulatives on sixth-grade students' learning interest, spatial visualization achievement, and learning responses. A quasi-experimental Matching Only Pretest–Posttest Control Group Design involved 58 sixth-grade students selected through purposive sampling, with 29 students in the experimental group and 29 in the control group. Data were collected using achievement tests, learning-interest and student-response questionnaires, observations, interviews, and documentation and analyzed using descriptive statistics, normality and homogeneity tests, paired- and independent-samples t-tests, normalized gain (N-Gain), and Cohen's d. Significantly higher learning-interest and posttest achievement scores were obtained by the experimental group than by the control group (p < .001). Moderate-to-high learning gains were achieved by 87.9% of students, while average student-response score reached 84.25%, indicating positive perceptions of the learning model. Inquiry-based learning supported by colorful cube manipulatives offers a promising approach for active, meaningful mathematics instruction. Findings should be interpreted considering intact classes from two schools, the absence of random assignment, and post-intervention measurement of learning interest. Results provide empirical evidence supporting the integration of structured inquiry and concrete manipulatives to enhance elementary students' spatial visualization, learning interest, and mathematics achievement.